Genomics-Assisted Crop Improvement Vol 2: Genomics Applications in Crops - Varshney, Rajeev K.; Tuberosa, Roberto (Springer Netherlands : Imprint: Springer, 2007)
Genomics research has great potential to revolutionize the discipline of plant breeding. This two-volume set provides a critical assessment of genomics tools and approaches for crop breeding. Volume 1, entitled "Genomics Approaches and Platforms", illustrates state-of-the-art genomics approaches and platforms presently available for crop improvement. Volume 2, entitled "Genomics Applications in Crops", compiles crop-specific studies that summarize both the achievements and limitations of genomics research for crop improvement. We hope that these two volumes, while providing new ideas and opportunities to those working in crop breeding, will help graduate students and teachers to develop a better understanding of the applications of crop genomics to plant research and breeding.